2015
DOI: 10.1111/bcpt.12385
|View full text |Cite
|
Sign up to set email alerts
|

Milrinone for the Treatment of Acute Heart Failure After Acute Myocardial Infarction: A Systematic Review and Meta‐Analysis

Abstract: Despite advancements in modern medicine, the treatment of acute heart failure (AHF) after acute myocardial infarction (AMI) remains challenging. Milrinone is effective in the treatment of chronic congestive heart failure, but its safety and efficacy in patients with AHF after AMI have not been systematically evaluated. This meta-analysis was performed to assess the safety and efficacy of milrinone in patients with AHF after AMI. We used a pre-designed protocol to search electronic databases for randomized tria… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
27
0
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(29 citation statements)
references
References 33 publications
(33 reference statements)
0
27
0
2
Order By: Relevance
“…Leki inotropowe, zwłaszcza te działające w mechanizmie adrenergicznym, mogą powodować tachykardię zatokową oraz wywoływać niedokrwienie mięśnia sercowego i zaburzenia rytmu serca, dlatego wymagane jest monitorowanie EKG w trakcie ich podawania. Istnieją wieloletnie wątpliwości pochodzące z badań, w których stosowano przerywane lub ciągłe wlewy z leków inotropowych, dotyczące zwiększania śmiertelności w AHF z powodu stosowania leków z tej grupy [559][560][561][562][563]575]. W każdym przypadku leki o działaniu inotropowym należy podawać ostrożnie, zaczynając od raczej małych dawek, zwiększając je w trakcie precyzyjnego monitorowania.…”
Section: Leki Inotropoweunclassified
“…Leki inotropowe, zwłaszcza te działające w mechanizmie adrenergicznym, mogą powodować tachykardię zatokową oraz wywoływać niedokrwienie mięśnia sercowego i zaburzenia rytmu serca, dlatego wymagane jest monitorowanie EKG w trakcie ich podawania. Istnieją wieloletnie wątpliwości pochodzące z badań, w których stosowano przerywane lub ciągłe wlewy z leków inotropowych, dotyczące zwiększania śmiertelności w AHF z powodu stosowania leków z tej grupy [559][560][561][562][563]575]. W każdym przypadku leki o działaniu inotropowym należy podawać ostrożnie, zaczynając od raczej małych dawek, zwiększając je w trakcie precyzyjnego monitorowania.…”
Section: Leki Inotropoweunclassified
“…
We read with a great interest the paper by Tang et al [1]. In this study, the authors identified that milrinone significantly improves cardiac function in patients with acute heart failure after acute myocardial infarction.
…”
mentioning
confidence: 93%
“…Three meta-analyses have evaluated milrinone in critically ill patients [35]. One meta-analysis included adult cardiac surgery patients and observed that milrinone was associated with a significant increase in mortality while an update of the review found no significant effects [4, 5].…”
Section: Introductionmentioning
confidence: 99%
“…One meta-analysis included adult cardiac surgery patients and observed that milrinone was associated with a significant increase in mortality while an update of the review found no significant effects [4, 5]. One other meta-analysis evaluated milrinone for the treatment of acute heart failure after acute myocardial infarction and suggested that milrinone might be safe and effective in these patients [3]. Unfortunately, only four trials with a limited number of 303 patients were included.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation